Clinical Manifestation and Treatment of Allergic Bronchopulmonary Aspergillosis - Agarwal, Ritesh; Muthu, Valliappan; Sehgal, Inderpaul S. (Seminars in Respiratory and Critical Care Medicine, 2023)
Allergic bronchopulmonary aspergillosis (ABPA) is a complex hypersensitivity reaction to airway colonization by Aspergillus fumigatus in patients with asthma and cystic fibrosis. The pathophysiology of ABPA involves a complex interplay between the fungus and the host immune response, which causes persistent inflammation and tissue damage. Patients present with chronic cough, wheezing, and dyspnea due to uncontrolled asthma. Characteristic symptoms include the expectoration of brownish mucus plugs. Radiographic findings often reveal fleeting pulmonary infiltrates, bronchiectasis, and mucus impaction. However, the definitive diagnosis of ABPA requires a combination of clinical, radiological, and immunological findings. The management of ABPA aims to reduce symptoms, prevent disease progression, and minimize the future risk of exacerbations. The treatment approach involves systemic glucocorticoids or antifungal agents to suppress the inflammatory response or fungal growth and prevent exacerbations. Biological agents may be used in patients with severe disease or glucocorticoid dependence. This review provides an overview of the clinical manifestations and current treatment options for ABPA.
Keywords: allergic fungal airway disease; allergic bronchopulmonary mycosis; ABPM; allergic fungal sensitization; corticosteroids; bronchiectasis